Why remember the First World War? - Turner, Paul (History through film, 2014)
Written to support the teaching of history skills in the 2014 National Curriculum, this First World War depth study will capture your students' interest while helping them to prepare for GCSE. 'Why Remember the First World War?' is the first in a new series called 'History Through Film' produced in partnership with British Pathé, and covers: the causes of the war, joining up, serving in the war, war methods, the home front, and the peace treaty. Each lesson in the Student Book has an integrated British Pathé film clip on Kerboodle. Each film clip comes with a fun, interactive worksheet designed to help your students analyse the film.